2019
DOI: 10.1364/ao.58.000c84
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the spectral excitation behavior of methane according to InP, GaSb, IC, and QC lasers as excitation source by sensor applications

Abstract: The MIR wavelength regime promises better gas detection possibilities than the NIR or the visible region because of the higher absorbencies simulated by HITRAN. In the MIR region are many important absorption lines of significant gases, which are relevant in healthcare, production supervision, and safety and environmental monitoring. One of those gases is methane. CH4 shows significant variations in absorbance with a maximum at 3.3 μm, which results in low detection limits in the range of low ppm. Interband-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…We have demonstrated that the amplifier can be used to improve the signal amplitude and signal/noise ratio. Similar sensitivity enhancement can be expected when more common photoacoustic spectroscopy is used [39,40].…”
Section: Discussionsupporting
confidence: 67%
“…We have demonstrated that the amplifier can be used to improve the signal amplitude and signal/noise ratio. Similar sensitivity enhancement can be expected when more common photoacoustic spectroscopy is used [39,40].…”
Section: Discussionsupporting
confidence: 67%